Optimal capital income taxation with tax evasion - Diego D'Andria (Kiel Institute for the World Economy (IfW), 2010)
The paper discusses the applicability of optimal taxation theory to source-based capital incomes when significant tax evasion is observed. Without tax evasion a modified Ramsey Rule may reduce distortions brought by international capital mobility, leading to levying differentiated tax rates in domestic sectors inversely proportioned to observed elasticities in terms of capital mobility. The introduction of tax evasion brings additional complexity. The viability of optimal tax rates à la Ramsey is explored, and additional requirement (namely that tax evasion is either very low or very homogeneous) are shown to be necessary in order to allow policy-makers to obtain the tax rates minimizing total excess burden. Results are also provided to solve the optimal taxation objective when tax evasion is a relevant phenomenon and is not homogeneous throughout domestic sectors.
Keywords: H21; H26; 330; optimal taxation; capital income taxation; tax evasion; Kapitalertragsteuer; Optimale Besteuerung; Steuerflucht; Theorie